Mapping the Strength & Productivity of Scientific Publications in North Sumatra Based on the Journal of Islamic Religious Education - Nurmawati Nurmawati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This research focuses on mapping the strength and productivity of scientific article publications in North Sumatra, which are based on journals that discuss the field of Islamic religious education. This study aims to identify scientific publications and mapping of journal information in the field of Islamic Religious Education (PAI) in North Sumatra. The data used in this study are the official websites of scientific journals based on the Open Journal System (OJS) published by universities that have a major or study program in Islamic Religious Education (PAI). The method used in this research is descriptive. The unit of analysis in this study is all research journals in the field of Islamic Education in North Sumatra which are indexed nationally and recorded on the Google search engine.The results of the mapping show that there is a significant information gap, unequal power and productivity of scientific publications in North Sumatra. In addition, this study also found that the productivity of scientific publications in the field of Islamic Studies in North Sumatra is still low